Inter-American Yearbook on Human Rights / Anuario Interamericano de Derechos Humanos, Volume 38 (2022) (VOLUME III) (Human Rights and Humanitarian Law E-Books Online, Collection 2024., 2025)
The 2022 Inter-American Yearbook on Human Rights provides an extract of the principal jurisprudence of the Inter-American Commission on Human Rights and the Inter-American Court of Human Rights. Part One contains the Decisions on the Merits of the Commission, and Part Two the Judgments and Decisions of the Court. The Yearbook is partly published as an English-Spanish bilingual edition. Some parts are in English or Spanish only. NB: This book is part of a four volume set. Vol. 1 ISBN: 978-90-04-71518-9 Vol. 2 ISBN: 978-90-04-71520-2 Vol. 3 ISBN: 978-90-04-71522-6 Vol. 4 ISBN: 978-90-04-53775-0 See Less